2005
DOI: 10.1152/ajpendo.00237.2005
|View full text |Cite
|
Sign up to set email alerts
|

Endurance training increases skeletal muscle LKB1 and PGC-1α protein abundance: effects of time and intensity

Abstract: Recent research suggests that LKB1 is the major AMP-activated protein kinase kinase (AMPKK). Peroxisome-proliferator-activated receptor-␥ coactivator-1␣ (PGC-1␣) is a master coordinator of mitochondrial biogenesis. Previously we reported that skeletal muscle LKB1 protein increases with endurance training. The purpose of this study was to determine whether training-induced increases in skeletal muscle LKB1 and PGC-1␣ protein exhibit a time course and intensity-dependent response similar to that of citrate synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 71 publications
7
55
2
1
Order By: Relevance
“…Here, our data suggest that LKB1 regulation of TRB3 expression occurs through the PGC1␣/PPAR␣ pathway in skeletal muscle. Previous reports on skeletal muscle have shown that increases in LKB1 protein with chronic exercise training (45) and activation of AMPK via AICAR (24,26,43) correlate with increases in PGC1␣ expression in skeletal muscle. Given that AMPK␣2 is required for the AICAR effect in skeletal muscle (24), it seems plausible that the reductions in AMPK␣2 activity in MLKB1KO muscle may partially mediate the decreases in PGC1␣ and PPAR␣ expression.…”
Section: Discussionmentioning
confidence: 88%
“…Here, our data suggest that LKB1 regulation of TRB3 expression occurs through the PGC1␣/PPAR␣ pathway in skeletal muscle. Previous reports on skeletal muscle have shown that increases in LKB1 protein with chronic exercise training (45) and activation of AMPK via AICAR (24,26,43) correlate with increases in PGC1␣ expression in skeletal muscle. Given that AMPK␣2 is required for the AICAR effect in skeletal muscle (24), it seems plausible that the reductions in AMPK␣2 activity in MLKB1KO muscle may partially mediate the decreases in PGC1␣ and PPAR␣ expression.…”
Section: Discussionmentioning
confidence: 88%
“…In rodents (2,15,34,46) and humans (33,44), acute exercise induces PGC-1␣ gene expression in muscle. It has been proposed that this increase in muscle PGC-1␣ expression after prolonged exercise mediates the insulin-sensitizing effects (16).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rodent models indicate that both short-term exercise and endurance training activate PGC-1α expression in skeletal muscle (34,35,64,65). Subsequent studies in humans have further demonstrated remarkable inducibility of PGC-1α in response to acute bouts of exercise or endurance training (38,66) and have indicated that PGC-1α levels are increased mainly in type IIa fibers after endurance training (66).…”
Section: Pgc-1 Signaling and Skeletal Musclementioning
confidence: 99%